Some Orientalist Doubts about the Actions of the Khulafay-e-Rashidun in Compiling the Sunna’a of the Prophet - Hanif, Mohammad Maaruf (Journal of Social Sciences - Kabul University, 2025)
Some Orientalist doubts about the actions of the Khulafay-e-Rashidun in compiling the Sunna’a of the Prophet. But there are two different views on the Sunna’ of the Holy Prophet. The first view: Mohaddesin are of the opinion that at the beginning of Islam, the Messenger of Allah forbade the writing of Sunna’s for some reasons and considerations, and then issued permission for it. Writing and drafting has been developed in the time of the Companions and some rules and regulations were set in this respect. As such the actions of the Khulafay-e-Rashidun led to the protection and preservation of Sunna’a. Second opinion: Orientalists raise some doubts about the collection and compilation of Sunna’a and about the performance of the Khulafay-e-Rashidun and pretend that these doubts are something accepted to all. In this article, we try to examine and study their doubts, particularly those about the performance of the Khulafay-e-Rashidun.